2022
DOI: 10.1098/rsif.2021.0659
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity determines the critical dynamics of biochemical networks

Abstract: Living systems comprise interacting biochemical components in very large networks. Given their high connectivity, biochemical dynamics are surprisingly not chaotic but quite robust to perturbations—a feature C.H. Waddington named canalization. Because organisms are also flexible enough to evolve, they arguably operate in a critical dynamical regime between order and chaos. The established theory of criticality is based on networks of interacting automata where Boolean truth values model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…This paper introduces the concept of regulatory nonlinearity as a new measure of characterization for Boolean networks. There are several other related characterizations of Boolean networks such as canalization [27], effective connectivity [10], symmetry [28] and controllability [29]. It has been previously reported that the levels of canalization (a measure of the extent to which fewer inputs influence the outputs of a Boolean function) and the mean effective connectivity (a measure of collective canalization) are high in biological networks [2, 10].…”
Section: Resultsmentioning
confidence: 99%
“…This paper introduces the concept of regulatory nonlinearity as a new measure of characterization for Boolean networks. There are several other related characterizations of Boolean networks such as canalization [27], effective connectivity [10], symmetry [28] and controllability [29]. It has been previously reported that the levels of canalization (a measure of the extent to which fewer inputs influence the outputs of a Boolean function) and the mean effective connectivity (a measure of collective canalization) are high in biological networks [2, 10].…”
Section: Resultsmentioning
confidence: 99%
“…This paper introduces the concept of regulatory nonlinearity as a new measure of characterization for Boolean networks. There are several other related characterizations of Boolean networks such as canalization [27], effective connectivity [10], symmetry [28] and controllability [29]. It has been previously reported that the levels of canalization (a measure of the extent to which fewer inputs influence the outputs of a Boolean function) and the mean effective connectivity (a measure of collective canalization) are high in biological networks [2,10].…”
Section: Broader Implicationsmentioning
confidence: 99%
“…There are several other related characterizations of Boolean networks such as canalization [27], effective connectivity [10], symmetry [28] and controllability [29]. It has been previously reported that the levels of canalization (a measure of the extent to which fewer inputs influence the outputs of a Boolean function) and the mean effective connectivity (a measure of collective canalization) are high in biological networks [2,10]. It has also been found that biological networks need few inputs to reprogram [30] and are relatively easier to control [3].…”
Section: Broader Implicationsmentioning
confidence: 99%
See 2 more Smart Citations